ANALISIS KEBIJAKAN TARIF EKSPOR LIMBAH CANGKANG KELAPA SAWIT INDONESIA KE JEPANG - Dhea Novita Agnesia; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Japan is one of Asian countries which uses palm kernel shell as raw material which used as bio energy. The demand of palm kernel shell in Japan is increasing up to 40% per year. Behind the high demand for japan, the Indonesian government has not set a renewable tariff, it makes the founders difficult to sell their products. This research is aimed to know the rationale of the decision made by the Indonesian government to set the export tariff of palm kernel shell in accordance with CPO cost.This research uses protectionism theory which is defined as the policy of governments which intentionally made to protect domestic producers from the international competitor. This theory is particularly relevant to the Indonesian government’s policies that have not been rigid in setting export tariff, because the export tariff of palm kernel shell which accordance with  the cost of CPO globally.The result of this research shows these followings facts. Firstly the Indonesian government wanted to redirect the sales to Perusahaan Listrik Negara (PLN), because the government prefer the use of Pembangkit Listrik Tenaga Biomassa (PLTBm) rather than Pembangkit Listrik Tenaga Uap (PLTU) due the fact that PLTBm is safer for the enviroment. Secondly, the government planned to upgrade the product of palm kernel shell to briquette (GVC). By producing briquette instead of palm kernel shell, Indonesia will export higher value products than the low-priced palm kernel shell. Thirdly, the government of Indonesia did not immediately create the regulation of the palm kernel shell export prohibition, instead the government of Indonesia creates the regulation of export control trough finance ministry regulation No.136/PMK.011/2015 and the fund management of palm plantation on finance ministry No.133/PMK.05/2015Keywords: CPO cost globally, export tariff, finance ministry regulation, green energy, palm kernel shell.